Enhancing Campus Connectivity: A Smart Intra-Transit Strategy for Efficient Vehicle Throughput - Kulkarni, Varad Sham; Jaibir, Bhairo Amankumar; Nayneshkumar, Patel Rudra; Pujara, Vraj; Chander, R. Vinob; Vegad, Himadri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
An advanced vehicle monitoring, and seat availability system is designed to monitor the vehicles from any source location A to destination location B in real time to the passengers. The proposed system would make good use of modern technologies via leveraging ultrasonic sensors, cloud API for example Thing Speak, and in-house Word Press software. The system track’s location, speed, and passenger count in real-time. This data fuels optimized scheduling and route planning, maximizing seat occupancy, and boosting overall productivity. A user-friendly dashboard visualizes vehicle activity within designated time slots, empowering faculty, and administrators with data-driven insights for improved resource allocation and scheduling. By comprehensively monitoring location, speed, and passenger count, the system ensures efficient Electric Vehicle operation within the campus confines, ultimately revolutionizing campus transportation and maximizing resource utilization.